Ischemic stroke and concomitant gastrointestinal complications- a fatal combination for patient recovery - Tuz, Ali A.; Hasenberg, Anja; Hermann, Dirk M.; Gunzer, Matthias; Singh, Vikramjeet (Frontiers in Immunology, 2022)
Stroke is primarily a neurodegenerative disease but can also severely impact the functions of other vital organs and deteriorate disease outcomes. A malfunction of the gastrointestinal tract (GIT), commonly observed in stroke patients, is often characterized by severe bowel obstruction, intestinal microbiota changes and inflammation. Over-activated immune cells after stroke are the major contributors to endorse intestinal inflammation and may induce damage to single-layer epithelial cell barriers. The post-stroke leakage of intestinal barriers may allow the translocation and dissemination of resident microflora to systemic organs and cause sepsis. This overshooting systemic immune reaction fuels ongoing inflammation in the degenerating brain and slows recovery. Currently, the therapeutic options to treat these GIT-associated anomalies are very limited and further research is required to develop novel treatments. In this mini-review, we first discuss the current knowledge from clinical studies and experimental stroke models that provide strong evidence of the existence of post-stroke GIT complications. Then, we review the literature regarding novel therapeutic approaches that might help to maintain GIT homeostasis and improve neurological outcomes in stroke patients.